The common law in colonial America. - Nelson, William Edward, 1940- (Oxford University Press, 2008)
In this four-volume series, the author shows how the legal systems of Britain's 13 North American colonies - initially established in response to divergent political, economic, and religious initiatives - slowly converged into a common American legal order that differed substantially from English common law.